A compilation on the contribution of the classic-curvature and the intensity-curvature functional to the study of healthy and pathological MRI of the human brain. (2015) - Ciulla, Carlo; Risteski, Filip A.; Veljanovski, Dimitar; Rechkoska, Ustijana Shikoska; Adomako, Edmund; Yahaya, Farouk
This paper places the emphasis on two intensity-curvature measurement approaches called: 1) classic-curvature (CC); 2) intensity-curvature functional (ICF) and makes a summary on the contribution of the CC and the ICF to the study of magnetic resonance imaging (MRI) of the healthy human brain and also of human brain tumors. The summary is structured referencing earlier related works and also adding evidence of the improvements to MRI imaging: 1) the CC changes the gray scale of the MRI; 2) the ICF shows the visually perceptible third dimension which can identify the tumor contour line; 3) the CC and the ICF are indeed filter masks, which determine two additional domains of the MRI image. Thus, the evidence makes this piece of work different from related research and also indicates that there are four domains in addition to the MRI where is possible to study both healthy and pathological human brains.